(untitled) (One Health & Risk Management, 2025)
Introduction. In the current healthcare context in Africa, numerous challenges remain to be addressed, including limited access to services, disparities in the quality of care, and inequalities in health outcomes. Furthermore, the lack of innovative business models capable of responding to the diverse and evolving needs of patients represents a major obstacle. This situation highlights the need to further integrate the patient’s experience into the design of healthcare services, which could transform traditional business models by incorporating a human-centered and experiential dimension. Material and methods. A systematic review of the existing literature was conducted to identify and synthesize the main contributions in this field. Results. We examined the fundamental principles of a business model that emphasizes patient experience, particularly in the healthcare sector in Africa. We also explored the factors influencing the economic functioning of these experience-based healthcare services. In addition, we analyzed the different ways in which these services are organized and marketed. Finally, we assessed how key performance indicators relate to various components of the experience-driven business model in healthcare. Conclusions. A theoretical framework will be developed to clarify the experiential business model and its implications for healthcare stakeholders, particularly regarding its design, promotion, and implementation.